JALUR INSTALASI LISTRIK SEBAGAI SISTEM TRANSMISI SINYAL AUDIO - Pambudi, Prastyono Eko (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2004)
Audio frequency represent an vibration voice which can be heard by human being, generally an completed system will contain a transmission with the information which transmission and a receiver yielding a replica or copy of input information released. In communications system which information transmission very relate to the modulation or time change of certain signal sinusoidal named by signal carrier. With a designing to develop the electronics apparatus which not expected complicated of installation of house electrics can be exploited for as media of transmission of signal audio from an peripheral to other peripheral. This matter cause the speaker not need the other, dissimilar transmission cables which long enough so that seen regular and natty.